Narratives of Heat and History - Simms, Maria (LiNQ (Literature in North Queensland), 2016)
Maria Simms reviews: Fish Lips, Carolyn van Langenberg. Indra Publishing, P 0 Box 7, Briar Hill, Victoria 3088, Australia. ISBN 0 9585805 9 6